Hypertensive Disorders during Pregnancy and Risk of Bronchopulmonary Dysplasia in Very Preterm Infants. - Rocha, GM (2019)
It is not yet fully known whether hypertensive disorders (HTD) during pregnancy impose an increased risk of development of bronchopulmonary dysplasia (BPD) in preterm newborn infants. OBJECTIVE:  To test the hypothesis that preeclampsia and other HTD are associated with the development of BPD in preterm infants. MATERIALS AND METHODS:  Data on mothers and preterm infants with gestational age 24 to 30 weeks were prospectively analyzed in 11 Portuguese level III centers. Statistical analysis was performed using IBM SPSS statistics 23. RESULTS:  A total of 494 preterm infants from 410 mothers were enrolled, and 119 (28%) of the 425 babies, still alive at 36 weeks, developed BPD. The association between chronic arterial hypertension, chronic arterial hypertension with superimposed preeclampsia, and gestational hypertension in mothers and BPD in preterm infants was not significant (p = 0.115; p = 0.248; p = 0.060, respectively). The association between preeclampsia-eclampsia and BPD was significant (p = 0.007). The multivariate analysis revealed an association between preeclampsia-eclampsia and BPD (odds ratio [OR] = 4.6; 95% confidence interval [CI] 1.529-13.819; p = 0.007) and a protective effect for BPD when preeclampsia occurred superimposed on chronic arterial hypertension in mothers (OR = 0.077; 95%CI 0.009-0.632; p = 0.017). CONCLUSION:  The results of this study support the association of preeclampsia in mothers with BPD in preterm babies and suggest that chronic hypertension may be protective for preterm babies.